Effects of endogamy on microsporogenesis in popcorn (Zea mays L.) - Maria Fernanda Piffer Tomasi Baldez da Silva; Eraldo Ferreira Lopes; Maria Suely Pagliarini; Carlos Alberto Scapim (Crop Breeding and Applied Biotechnology, 2007)
Inbred lines are necessary for the development of popcorn hybrids. Genes for several traits, among them thoserelated to the meiotic process, approach homozygosis during inbreeding. The purpose of this paper was to evaluate themeiotic stability of popcorn endogamic lines developed from a triple hybrid in contribution to hybrid breeding programs. Theoriginal population (S0) and seven annual self-pollinated generations (S1 to S7) were analyzed. Cytological results werestatistically analyzed by linear regression. The frequency of total and terminal chiasmata decreased with endogamy. Meioticabnormalities also increased with endogamy although their number was not high. Since the frequency of abnormalities waslow and did not affect drastically the meiotic product, inbred lines from the hybrid under analysis may have a high potentialfor the establishment of new popcorn hybrids.